Strategic Readiness of 6G Implementation in Indonesian Telco Company : an Internal And External Environment Analysis - Angela Merici Diah Larasati; Sahat Hutajulu (Green Publisher Indonesia, 2025)
When it comes to paving the way for innovation in B2B telecommunication services for companies in Indonesia, the prospect of Indonesia integrating a digitally driven economy and 6G connectivity is essential. This research analyzes the strategic readiness of one of Indonesian Telco Company to leverage 6G technology for scaling up its B2B service offerings. Data gathering was done through semi-structured interviews with important stakeholders alongside secondary materials while a qualitative explorative approach was utilized. Internal strengths and weaknesses were analyzed through SWOT analysis while PESTEL and Porter’s Five Forces frameworks assessed external opportunities and threats. The results indicate that the firm’s infrastructural prowess and group synergy positioning are major boons, but challenges such as ROI lucidity, competitive agility, and talent development remain significant issues. This work offers insights for stearing technological spendings in a regulated investment landscape while enabling the strategic foresight telecommunication investments in Indonesia on 6G deployment in the sector.